One grain of rice : a mathematical folktale - Demi. (New York : Scholastic Press, 1997)
A reward of one grain of rice doubles day by day into millions of grains of rice when a selfish raja is outwitted by a clever village girl.
Keywords: Folklore -- India; Mathematics -- Folklore